Italy: The Real Effects of Inflation and Disinflation - Francesco Giavazzi; Luigi Spaventa (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1989)
The Italian economy has often puzzled foreign observers over the past fifteen years. In this article we attempt to interpret these developments. In our interpretation, some implications of which are perhaps of more than local interest, we stress the role of policies throughout the period.
Keywords: 330